PENGARUH PENGETAHUAN, TEKANAN KETAATAN DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT INTERNAL AUDITOR PEMERINTAH - Dian Priatiningsih (Fakultas Ekonomi Universitas Pekalongan, 2018)
This study aims to examine and to obtain empirical evidents on effect of knowledge, obedience pressure and task complexity to audit judgment of government internal auditor. The advantages of this research is to use internal auditors Inspectorate District that is rarely used by other research. The dependent variable in this research is that judgments of audit quality is measured using a questionnaire instrument, while the independet variable is knowledge, obedience pressures and task complexity. This research that the internal auditor on the Inspectorate District in Pemalang, Tegal and Pekalongan. Sample of research with the 45 respondents in 2017. Type of data in this study are primary data using questionnaires. The results showed that the knowledge, task complexity and obedience pressures have a positif but not significant effect to audit judgments.Keywords: audit judgments, knowledge, obedience pressures and task complexity